COMPARATIVE EVALUATION OF HISTOLOGICAL RESULTS OF MODERN FIRE INFLAMMATORY INJURIES OF THE COLUMN BY DIFFERENT TYPES OF BULLETS IN THE EXPERIMENT - Tsymbalyuk, V.I.; Lurin, I.A.; Chaikovskyi, Yu.B.; Graboviy, O.M.; Gumenyuk, K.V.; Nehoduiko, V.V.; Makarov, V.V. (World of Medicine and Biology, 2022)
The article shows the study results of the colon pathomorphosis peculiarities in gunshot wounds in experimental animals (pigs). Semi-quantitative assessment of the hemorrhage volume in the area of intestinal vessels in the own plate of the mucous membrane and in the submucosal base was performed on the recorded digital images of micropreparations. Histological examination of the colon damaged by bullets of the same calibre but with different properties showed significant morphological changes in the colon wall around the site of injury. The authors have shown that the changes in the colon are significantly more pronounced when using a 5.45 V-Max bullet with a larger area of damage than in the 5.45 PS bullet.
Keywords: gunshot wound; colon; pig